Gone and forgotten - Hallowes, Lari Chanel (Rhodes University, 2026)
Cemeteries, more than simply spaces to bury the dead, are landscapes that function as sites of memory, reflecting a community’s values through the ways they have chosen to commemorate their dead. This thesis engages with the question of how certain cemeteries become forgotten from public memory and heritage in South Africa. It explores how certain burial spaces are commemorated by the state for political purposes in the present, and how, inversely, the burial spaces that do not serve the goals of the state may become forgotten through their exclusion from commemoration. Using three case studies of historically significant but forgotten black cemeteries from Gqeberha (formerly Port Elizabeth) in the Eastern Cape, this thesis analyses how state-sponsored public memory and heritage projects which prioritise particular categories of the dead or burial sites, may lead to the exclusion or forgetting of others. This is relevant as being represented in public memory signifies recognition and legitimacy, while being forgotten suggests that some lives and histories are regarded as less significant than others.
public memory, heritage, and missing black cemeteries in Gqeberha
Keywords: Cultural property (http://id.loc.gov/authorities/subjects/sh97000183); Cemeteries--South Africa (http://id.loc.gov/authorities/subjects/sh87001621); Gqeberha (South Africa) (http://id.loc.gov/authorities/names/no2025073395); Collective memory (https://www.wikidata.org/wiki/Q254217)